Metabharata Game Based on Javanese Wayang Art Using Unity - Addaviqi, Iqbal Izza; Prapanca, Aditya (Universitas Negeri Surabaya or The State University of Surabaya, 2024)
The development of the 2D game Metabharata was initiated as an effort to introduce and preserve the art of Javanese puppetry, especially to the younger generation. Javanese wayang, with its deep artistic and philosophical values, is considered to have the potential to be creatively conveyed through the medium of 2D games. This research applies the Waterfall model development method to ensure a structured approach in the creation process. The Metabharata game is geared towards bringing together digital technology, structured software development methods, and the rich cultural arts of Javanese wayang. The testing of this game involved content validity analysis, construct validity through a multi-expert approach, and usability testing with the USE Questionnaire. The validity results showed a very valid level of validity, and usability testing showed high satisfaction with a usability percentage of 94%. With these results, it can be concluded that ‘Metabharata’ is worth maintaining and developing further as a contribution to the development of local culture-based games.